If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 4 + 3x = 4 Reorder the terms: 4 + -2x + 3x = 4 Combine like terms: -2x + 3x = 1x 4 + 1x = 4 Add '-4' to each side of the equation. 4 + -4 + 1x = 4 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = 4 + -4 1x = 4 + -4 Combine like terms: 4 + -4 = 0 1x = 0 Solving 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = 0 Simplifying x = 0
| 6+2(3j+2)=4(1+j) | | 7p-12=-2 | | -10x+58+6x+41=111 | | 6-9x=5x-9x-29 | | [7x-10]=73 | | 5x-14=-2x+15 | | -6+8p=-16+4p | | x=-5y-7 | | 2-(-x)=-4 | | -5=-5(2n-3) | | 4a^3-25a=0 | | -29=7x-5-x | | -4(x-5)=-7+28 | | 3y-3=13y+77 | | 6w^2+16w+8=0 | | 21x-8=5(4x+2)-2 | | 9=24-3p | | 12+n-2+6n=n-2+8n | | 10x+1=2(3x+9)-1 | | 25x(x+5)+10y=6.50 | | 2x+7-3x=x+21 | | 3x+1+5x-3=90 | | 6y-9y=21 | | w=56+(22+3) | | -6x+8=-2x+32 | | 6k-6k=-8+k | | (1)(4)x+10=2 | | 4(2+x)=3(x-9) | | 1+4x-8=-15 | | -r-(1+r)=-9+6r | | 21x-8=5(4x+2)+2 | | 14x+7=105 |